Factors Affecting the Internationalization of Small and Medium-sized Enterprises in South Korea: Entrepreneurial Orientation, Human Capital and Technological Capabilities - Kim, Kang-Sik (International Journal of Economics and Financial Issues, 2017)
Internationalization provides SMEs with many strategic benefits. However, for many SMEs it is not easy to carry out internationalization successfully due to limited resources and capabilities. In order to accomplish an efficient and effective internationalization, it is crucial to grasp the determinants of SME internationalization and their relationship to the firm internationalization. This paper investigates the factors affecting the degree of internationalization of SMEs in South Korea. This study further explores how the international orientation of entrepreneur, the employee human capital, the technological capabilities of a firm, and the external environment might explain the degree of SME internationalization. The findings indicate that entrepreneurial orientation and investment in employee human capital are the critical factors for explaining the internationalization of South Korean SMEs. In addition, we find that technology turbulence and market similarity moderate these relationships, based on the analysis of data collected from 150 South Korean SMEs. The results imply that managers of SMEs should consider these internal and external factors in order to enhance their performance in international markets. Keywords: internationalization, SMEs, entrepreneur orientation, human capital, Korea JEL Classification: F23, M13, O15